(untitled) (Encuentros, 2021)
In this article, we address the composition and deployment of the performance called Bodies-plastic, which emerges from a research-creation process, in which we toured and intervened in various spaces in the city of Medellín, Colombia. In this research, we proceeded from orientations that make the experience of the body in space a methodological lens to understand what happens there. Therefore, the Bodies-plastic performance is an artistic composition as well as an epistemological materialization which intends to intervene and circulate the knowledge that was being produced in the investigation. This process led us to conclude that by piercing some of the city’s envelopes, critical aspects of the social model that we have established are glimpsed. Likewise, we observe that downtown Medellín tends to be inhabited through bubbles, which touch, fissure and recompose themselves, seeking to maintain that envelope that is believed to isolate from the presence of others.